(untitled) (Al-Academy, 2025)
Websites have contributed to providing opportunities and ideas to individuals, and have changed their lifestyles all over the world, as they can now communicate and interact with each other wherever they are. Men’s clothing is considered one of the most consumed pieces of clothing because of its special importance in the lives of men in Saudi society, as it is one of the clothing products that has a historical dimension, and the manufacture of men’s clothing depends on various factors, some of which are economic and some of which are closely linked to the method used in production. Therefore, the men’s clothing industry is one of the industries that has received great attention from producers. Medium-sized projects contribute to providing job opportunities and supporting the spread of the culture of self-employment among female graduates instead of relying on government jobs. Their importance is represented by their contribution to economic and social development, in addition to their role in preparing women entrepreneurs. The research aims to : 1- Designing a website to train female graduates on manufacturing men’s clothing according to technical regulations to enrich the field of medium-sized projects. 2- Measuring the effectiveness of the website in providing female graduates with special knowledge for manufacturing men’s clothing in accordance with technical regulations. 3- Measuring the effectiveness of the website in providing female graduates with the special skills to manufacture men’s clothing according to technical regulations. The research recommended : 1-Developing academic curricula in educational institutions according to new technology to meet the rapid global changes in human resources development. 2- Activating electronic educational means to raise the skill level of female students to bring Saudi educational outcomes to international levels. 3- Creating specialized websites to draw clothing models for different categories, “women, men, children,” so that female students can integrate into the labor market and establish small and medium projects of their own. 4- Holding training courses for college graduates to train on men’s clothing manufacturing skills according to scientific principles.